2016
DOI: 10.3892/or.2016.5320
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-302a targets GAB2 to suppress cell proliferation, migration and invasion of glioma

Abstract: Glioma is the most frequent and aggressive primary tumor of the brain in humans. Over the last few decades, significant progress has been made in early detection and multi-mode treatments, but the prognosis of gliomas is still extremely poor. MicroRNAs are endogenously expressed non-coding, single strand and short RNA molecules. Increasing number of studies demonstrated that microRNAs are dysregulated in a variety of human cancers, and play significant roles in tumorigenesis and tumor development, including gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…We then focused specifically on miRNA-320a, which was recently shown to act as a tumor suppressor in different cancer types in which it was found downregulated, such as colorectal 30 , 31 , breast 32 , 33 , bladder 34 , lung 35 37 , prostate 38 and gastric cancer 39 , 40 , multiple myeloma 41 and gliomas 42 44 .…”
Section: Discussionmentioning
confidence: 99%
“…We then focused specifically on miRNA-320a, which was recently shown to act as a tumor suppressor in different cancer types in which it was found downregulated, such as colorectal 30 , 31 , breast 32 , 33 , bladder 34 , lung 35 37 , prostate 38 and gastric cancer 39 , 40 , multiple myeloma 41 and gliomas 42 44 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that overexpression of miR-497 is associated with resistance to temozolomide in human glioma cells by targeting mammalian target of rapamycin/B-cell lymphoma 2 (26). It has also been reported that miR-302a is an important tumor suppressor of glioma progression by directly targeting GRB2-associated binding protein, thus providing novel insight into the molecular mechanisms underlying the genesis, development and progression of glioma (27). Furthermore, miR-128-3p was reported to be closely associated with lung cancer (13), hepatocellular carcinoma (14,15) and gastric cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…gastric cancer (18), hepatocellular carcinoma (19), prostate cancer (20), renal cell carcinoma (21), glioma (22) and lung cancer (23). Moreover, numerous studies reported that the dysregulation of miRNAs is involved in tumorigenesis and tumor development; some miRNAs act as an oncogene or tumor suppressor gene in human cancers, depending on the regulated tumor forms and their specific target genes (24).…”
Section: Microrna-379 Acts As a Tumor Suppressor In Non-small Cell Lumentioning
confidence: 99%